A Deep-Hole Microdrilling Study of Pure Magnesium for Biomedical Applications - Margherita Pizzi; Francesco De Gaetano; Marco Ferroni; Federica Boschetti; Massimiliano Annoni (Micromachines, 2023)
The mechanisms of deep-hole microdrilling of pure Mg material were experimentally studied in order to find a suitable setup for a novel intraocular drug delivery device prototyping. Microdrilling tests were performed with 0.20 mm and 0.35 mm microdrills, using a full factorial design in which cutting speed <semantics>vc</semantics> and feed <semantics>fz</semantics> were varied over two levels. In a preliminary phase, the chip shape was evaluated for low feeds per tooth down to 1 μm, to verify that the chosen parameters were appropriate for machining. Subsequently, microdrilling experiments were carried out, in which diameter, burr height and surface roughness of the drilled holes were examined. The results showed that the burr height is not uniform along the circumference of the holes. In particular, the maximum burr height increases with higher cutting speed, due to the thermal effect that plasticizes Mg. Hole entrance diameters are larger than the nominal tool diameters due to tool runout, and their values are higher for high <semantics>vc</semantics> and <semantics>fz</semantics>. In addition, the roughness of the inner surface of the holes increases as <semantics>fz</semantics> increases.